Micropropagation and Subsequent Enrichment of Carotenoids, Fatty Acids, and Tocopherol Contents in Sedum dasyphyllum L - Park, Han Yong; Saini, Ramesh Kumar; Gopal, Judy; Keum, Young-Soo; Kim, Doo Hwan; Lee, Onew; Sivanesan, Iyyakkannu (Frontiers in Chemistry, 2017)
A promising micropropagation protocol has been systematically established and demonstrated for the enhanced production of carotenoids, tocopherol and fatty acids in shoot tissues of Sedum dasyphyllum. Shoot tip explants were grown on Murashige and Skoog (MS) medium. Different concentrations of N6-benzyladenine (BA) or thidiazuron (TDZ) alone or in combination with α-naphthaleneacetic acid (NAA) were tested in order to stimulate multiple shoot production. Ideal shoot induction (100%) and maximized shoot numbers (36.4) were obtained on explants cultured on media incorporated with 2 μM BA and 1 μM NAA combinations. The in vitro-developed shoots rooted best on half-strength MS media incorporated with 2 μM indole 3-butyric acid. Plantlets were effectively acclimatized in the greenhouse with 100% survival rate. The composition and contents of bioactive compounds such as carotenoids, tocopherol and fatty acids in shoot tissues of S. dasyphyllum were investigated using HPLC and GC-MS. The most abundant carotenoid in the shoot tissue was all-E-lutein (40.3–70.5 μg g−1 FW) followed by 9′-Z-neoxanthin (5.3–9.9 μg g−1 FW), all-E-violaxanthin (4.4–8.2 μg g−1 FW), and all-E-β-carotene (1.6–3.6 μg g−1 FW). The α-tocopherol contents of in vitro-raised shoots was 6.5-fold higher than shoots of greenhouse-grown plants. The primary fatty acids found in shoot tissues were α-linolenic acid (32.0–39.3%), linoleic acid (27.4–38.2%), palmitic acid (13.3–15.5%), and stearic acid (5.2–12.2%). In all, summarizing the findings, the micropropagated S. dasyphyllum showed significant enrichment of valuable bioactive carotenoids (92.3 μg g−1 FW), tocopherols (14.6 μg g−1 FW), and α-linolenic acid (39.3%) compared to their greenhouse counterparts. The protocol demonstrated here could be applied for the mass propagation and production of enhanced bioactive compounds from S. dasyphyllum with credibility.